Persistent organic pollutants sorbed in plastic resin pellet - "Nurdles" from coastal areas of Central Chile - Pozo, Karla; Urbina, Williams; Gómez, Victoria; Torres, Mariett; Nuñez, Dariela; Přibylová, Petra; Audy, Ondřej; Clarke, Bradley; Arias, Andrés; Tombesi, Norma; Guida, Yago; Klánová, Jana (Marine pollution bulletin, 2020)
Plastic resin pellets were collected from coastal areas (n = 7) of central Chile. Pellets were analyzed using Fourier-transform infrared spectroscopy for polymer identification and gas chromatography-mass spectrometry for Persistent Organic Pollutants (POPs) determination. Screened compounds were PBDEs (n = 10), PCBs (n = 7), and OCPs (n = 13). Pellets were only found at Lenga Beach (San Vicente Bay), which is likely influenced by the presence of industrial activities in the surrounding coastal area. The diameter of the pellets was 4.0 ± 0.6 cm (n = 370), the color varied from white (32%) to yellowing (68%), and the most prevalent polymer identified was high-density polyethylene (99%). POPs concentrations (ng/g-pellet) ranged from 10 to 133 for Ʃ10PBDEs, from 3 to 60 for Ʃ7PCBs and between 0.1 and 7 for DDTs. Levels of POPs are consistent with other investigations around the world and highlight the sorbtion capacity of plastics resin pellets, and consequently transport of POPs into coastal environments.
Keywords: chemické látky znečišťující vodu; Pellets; plastické hmoty; Chile; San Vicente Bay; Plastics; monitorování životního prostředí; Environmental Monitoring; Microplastics; látky znečišťující životní prostředí; Water Pollutants, Chemical; POPs; polychlorované bifenyly; Environmental Pollutants; Polychlorinated Biphenyls